Modeling of mixing bread dough process using computational techniques - Luchian, Mihaela; Stefanov, Stefan; Litovchenko, Igor; Mihaylov, Ivan; Hadzhіyskі, Vіlhelm (My University, 2012)
Mixing is a crucial operation in the bakery industry. The bread dough is a very complex material, considered viscoelastic whose behavior depends on moisture content and temperature. This article aim is to develop advanced technology for modeling bread dough mixing, in order to provide a predictive capability of optimum design parameters of dough mixers using computational techniques.
Keywords: змішування; тісто; моделювання; flow vision; mixing; bread dough; modeling; simulation; кафедра машин і апаратів харчових та фармацевтичних виробництв